MANAJEMEN MODAL KERJA DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Setyanto, Adrianus Dhimas (Jurnal Akuntansi AKUNESA, 2014)
This study aims to determine the effect of working capital management on firm value. The sample used is a program participant Corporate Governance Perception Index (CGPI) during the period from 2003 to 2011 and is listed on the Indonesia Stock Exchange (IDX). The results showed that the working capital management has an influence on the value of the firm. However, corporate governance variables failed to moderate the relationship between working capital management and enterprise value. It shows that control from the Indonesian government to the corporate governance principles implementation was still weak. Keywords: Working Capital Management, Cash Conversion Cycle, Corporate Governance, Firm Values??.